Keunggulan Bersaing melalui Orientasi Pasar, Kemampuan Jejaring, dan Inovasi pada Usaha Kecil dan Menengah (UKM) di Jawa Timur - Nikmah, Farika; Hasan, Halid; Sidanti, Heny (Jurnal Manajemen Bisnis dan Keuangan, 2025)
Small and Medium Enterprises (SMEs) play a vital role in Indonesia’s economy. The dynamic market conditions demand that SMEs achieve competitive advantage to ensure the sustainability of their businesses. Strategies to attain such advantage can be developed by strengthening market orientation, networking capability, and innovation. This study analyzes the direct influence of market orientation, networking capability, and innovation on the competitive advantage of SMEs in East Java. A quantitative approach was employed, with data collected through questionnaires distributed to SMEs in East Java in collaboration with the Integrated Business Service Center (PLUT) in Batu City, Malang Regency, Tulungagung Regency, and Mojokerto Regency. PLUT is an institution that assists SMEs in expanding market access. A total of 600 questionnaires were distributed, and 552 were deemed valid for analysis. The data were analyzed using multiple linear regression methods. The findings reveal that the competitive advantage of SMEs is significantly influenced by market orientation, which provides the most dominant contribution, followed by innovation and networking capability. These findings offer valuable insights for SMEs in formulating effective strategies to achieve competitive advantage, enabling them to face increasing competition and adapt to the global market.